Final answer:
The expression !(a > b || b <= c) is equivalent to a <= b && b > c, as shown by distributing the negation symbol and simplifying each part of the expression.
Step-by-step explanation:
The given expression is !(a > b || b <= c). To determine the equivalent expression, we can distribute the negation symbol to each part of the expression. This gives us (!(a > b)) && (!(b <= c)). Now we can simplify each part:
1. !(a > b) is equivalent to a <= b. This means that if a is not greater than b, then it must be less than or equal to it.
2. !(b <= c) is equivalent to b > c. This means that if b is not less than or equal to c, then it must be greater than it.
Combining the simplified parts, we get a <= b && b > c. Therefore, the given expression is equivalent to c. a <= b && b > c